Market Reaction to MUI Fatwa on Boycott: Evidence from Retail Companies Listed on the Indonesia Stock Exchange - Amina Hi Badarudin, Siti; Hadady, Hartaty; Amiro, Suratno (Jurnal MS, 2025)
Objective: This study aims to examine the effect of abnormal return and trading volume activity before and after a specific event in the capital market. The research seeks to determine whether the event generates significant differences in stock performance indicators, reflecting market reaction and efficiency. Methodology: This study employed an event study approach using quantitative methods. The sample consisted of 10 observations (N = 10) covering stock abnormal returns and trading volume activities before and after the event. Data were processed using SPSS with Paired Samples Test to assess the differences between the two periods. Descriptive statistics were also applied to capture variations in minimum, maximum, mean, and standard deviation values across the observed variables. Findings: The results indicate that there is no significant difference in abnormal return before and after the event, as evidenced by a two-tailed p-value greater than 0.05. This suggests that the capital market remains relatively efficient, and investors do not obtain abnormal returns during the observation period. Conversely, trading volume activity shows a one-tailed significance, implying that the event influences market activity if the research hypothesis is directional. However, the two-tailed test demonstrates that the effect is not statistically significant in a non-directional context. Conclusion: The findings reveal that the event has a stronger impact on trading volume activity than on abnormal returns, which remain relatively stable. These results highlight the importance of considering the directional hypothesis in capital market event studies and reinforce the notion of market efficiency in processing information. Keyword: Abnormal Return, Trading Volume Activity, Event Study, Market Efficiency.